Purification and biochemical characterization of two xylanases produced by Aspergillus caespitosus and their potential for kraft pulp bleaching - Sandrim, V.C.; Rizzatti, A.C.S.; Terenzi, H.F.; Jorge, J.A.; Milagres, A.M.F.; Polizeli, M.L.T.M. (Process biochemistry (1991), 2005)
Two extracellular xylanases produced by the thermotolerant fungus Aspergillus caespitosus grown in sugar cane bagasse were purified and characterized. Estimated molecular masses were 26.3 and 27 kDa (xyl I); 7.7 and 17.7 kDa (xyl II) for gel filtration and SDS-PAGE, respectively. Optimal temperature for both xylanases was 50–55 °C. Optimal pH was 6.5–7.0 for xyl I, and 5.5–6.5 for xyl II. The thermostability ( T half) at 55 °C was 27.3 min (xyl I) and >90 min (xyl II). Xylanase activity was inhibited by several ions. β-mercaptoethanol activated 59 and 102% xyl I and xyl II activities, respectively. These enzymes preferentially hydrolyzed birchwood xylan, and the K m and V max values were 2.5 mg/ml and 1679 U/mg protein (xyl I), and 3.9 mg/ml and 113 U/mg protein (xyl II). The action of both xylanases mainly that of xyl II, on kraft pulp reduced kappa number and increased pulp viscosity.